Phosphatidylethanolamine homeostasis under conditions of impaired CDP-ethanolamine pathway or phosphatidylserine decarboxylation - St Germain, Michaela; Iraji, Roya; Bakovic, Marica (Frontiers in Nutrition, 2023)
Phosphatidylethanolamine is the major inner-membrane lipid in the plasma and mitochondrial membranes. It is synthesized in the endoplasmic reticulum from ethanolamine and diacylglycerol (DAG) by the CDP-ethanolamine pathway and from phosphatidylserine by decarboxylation in the mitochondria. Recently, multiple genetic disorders that impact these pathways have been identified, including hereditary spastic paraplegia 81 and 82, Liberfarb syndrome, and a new type of childhood-onset neurodegeneration-CONATOC. Individuals with these diseases suffer from multisystem disorders mainly affecting neuronal function. This indicates the importance of maintaining proper phospholipid homeostasis when major biosynthetic pathways are impaired. This study summarizes the current knowledge of phosphatidylethanolamine metabolism in order to identify areas of future research that might lead to the development of treatment options.